Safety and immunogenicity of an Escherichia coli-produced bivalent human papillomavirus type 6/11 vaccine: A dose-escalation, randomized, double-blind, placebo-controlled phase 1 trial. Issue 6 (30th November 2022) - Mo, Zhao-Jun; Bi, Zhao-Feng; Sheng, Wei; Chen, Qi; Huang, Teng; Li, Ming-Qiang; Cui, Xue-Lian; Wangjiang, Ya-Hui; Lin, Bi-Zhen; Zheng, Feng-Zhu; Sun, Guang; Li, Ya-Fei; et al.
ABSTRACT: A dose-escalation, randomized, double-blind, placebo-controlled phase 1 clinical trial enrolled 145 eligible participants aged 18–55 years in March 2015 in Liuzhou, China. Stratified by age and sex, the participants were randomly assigned to receive either 30, 60, or 90 μg of the HPV-6/11 vaccine (n = 41/40/40) or the parallel placebo vaccine (n = 8/8/8) with a 0/1/6-month dose-escalation schedule. Participants were actively followed-up to record local and systemic AEs occurring within 30 days after each vaccination, and SAEs occurred in 7 months. Blood and urine samples of each participant were collected before and 2 days after the first and third vaccination to determine changes in routine blood, serum biochemical, and urine indexes. Serum HPV-6/11-specific IgG and neutralizing antibody levels at month 7 were analyzed. A total of 79 adverse events were reported, and no SAEs occurred. The incidences of total adverse reactions in the 30 μg, 60 μg, and 90 μg HPV vaccine groups and the control group were 31.7%, 50.0%, 42.5%, and 62.5%, respectively. All but one of the adverse reactions was mild or moderate with grade 1 or 2. No vaccine-related changes with clinical significance were found in paired blood and urine indexes before and after vaccinations. All the participants in the per-protocol set seroconverted at month 7 for both IgG and neutralizing antibodies. The candidate novel Escherichia-coli -produced bivalent HPV-6/11 vaccine has been preliminarily proven to be well tolerated and with robust immunogenicity in a phase 1 clinical study, supporting further trials with larger sample size. The study has been registered at ClinicalTrials.gov (NCT02405520)